Local skin reactions and the onset of influenza-like signs and symptoms induced by imiquimodCapsule Summary - Neal Bhatia, MD (Elsevier, 2022)
Background: Since the introduction of imiquimod cream, patients have reported treatment-emergent symptoms that mimic influenza. However, clear relationships between the onset of symptoms from topical imiquimod and various variables (eg, patient's age) remain unclear. Objective: To evaluate potential relationships between the onset of visceral symptoms that mimic influenza and variables including patient age, the severity of local cutaneous reactions, the amount of surface area, areas of the body being treated, and serum levels of inflammatory cytokines present during 2 cycles of 14-day treatment of imiquimod 3.75% cream. Methods: In this single-center, open-label, investigator-initiated trial, 22 patients with 5-20 actinic keratosis were stratified into 1 of 2 age groups: ages 30-59 and ages 60-89. Results: Although the occurrence of systemic symptoms was infrequent during the treatment period, the majority of patients who reported local skin reactions preceding systemic symptoms developed them within 7-11 days of the treatment cycle. Levels of circulating cytokines had no predictive value. Limitations: This study was limited by its small sample size as well as the small number of cytokines evaluated. Chemokines and cytokines beyond those evaluated may contribute to influenza symptoms and/or systemic responses to imiquimod. Conclusion: The onset of local skin reactions may serve as a predictor for the potential onset of systemic symptoms that mimic those of influenza and could be used as a talking point for patients, though further research is needed.